Partial Label Learning via Conditional-Label-Aware Disambiguation - Ni, Peng; Zhao, Su-Yun; Dai, Zhi-Gang; Chen, Hong; Li, Cui-Ping (Journal of computer science and technology, 2021)
Partial label learning is a weakly supervised learning framework in which each instance is associated with multiple candidate labels, among which only one is the ground-truth label. This paper proposes a unified formulation that employs proper label constraints for training models while simultaneously performing pseudo-labeling. Unlike existing partial label learning approaches that only leverage similarities in the feature space without utilizing label constraints, our pseudo-labeling process leverages similarities and differences in the feature space using the same candidate label constraints and then disambiguates noise labels. Extensive experiments on artificial and real-world partial label datasets show that our approach significantly outperforms state-of-the-art counterparts on classification prediction.